Penerapan Metode Eksperimen Dan Model Pembelajaran Kooperatif Untuk Meningkatkan Hasil Pembelajaran IPA Dalam Mendeskripsikan Sifat-Sifat Cahaya Pada Siswa Kelas V SD - Mulyati, Sri (Universitas Sebelas Maret, 2020)
This report is motivated by the findings in the field where the condition of the fifth grade students of SDN Negla 03 has the characteristics of relatifely low learning outcomes in science learning in the basic competency “Describe the Properties of Light”. One alternative to help improve learning outcomes. The authors make improvements through the applications of eksperimental methods and cooperative learning models. This report describes the implementation and results of research onimproving learning on the use of eksperimental methods and cooperative learning models.The research used the CAR method which was carried out in 2 cycles. Each cycle consists of four stages including planning, implementation, observation and reflection. The subject of this research is the fifth grade student of SDN Negla 03. The instruments used in this research are qualitative and quantitative data. Qualitative data obtained trough student and teacher activity observation sheets, while quantitative data were obtained through formative tests. The results showed an increase in learning outcomes along with the increase in student activity, motivation and cooperation in learning. Thus, the application of cooperative learning models can improve student learning outcomes.